Concentration dependent diffusivities of model solvents in heavy oil - Mohan, Vijitha; Neogi, P.; Bai, Baojun (Diffusion Fundamentals, 2017)
The rates of dissolution of heavy crude oil in liquid solvents and rates of desorption of solvents from oil have been measured. The crude oil used is a non-volatile heavy oil of 4253 mPa.s viscosity at room temperature. The solvents used are hexane, heptane and toluene. When the oil (black) is contacted with a solvent (transparent) an interface is seen which moves with time and takes a very long time to become fuzzy. The rate of movementof the front is measured. The dissolution experiments give very consistent results, but there are two parameters involved, Do, the diffusivity at infinite dilution and alpha which determines the concentration dependence. As a result it is necessary to do desorption experiments to be able to calculate both constants from the rate of movement of the front data. However, desorption experiments could not be performed under conditions of low concentrations suitable for the present case because of the very viscous nature of the oil. As a result, although the desorption experiments also showed good results, they could not be used to obtain good values of the parameters. When Stokes-Einstein equation was used to calculate Do, excellent results were obtained with alpha ~ 10 for the dissolution experiments and good deal smaller for the desorption experiments. That result is used to conclude that the above form for concentration dependent diffusivity is correct and concentration dependence is very high at low solvent concentrations explaining the sharp interfaces during dissolution.Other evidences have also been offered.